2014
DOI: 10.31384/jisrmsse/2014.12.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Population and Poverty Nexus in Pakistan

Abstract: Pakistan has one of the highest population growth rates in the world. Rapid population growth is the bone of contention as well as the crux of the problems. 80 million people live below the poverty line. Macroeconomic instability, rising absolute and relative poverty and worsening income inequalities are the direct as well as indirect result of the high population growth. Population pressures are threatening land, forests and water resources. Improvement in operation and implementation of the family planning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…High population growth has become an important limiting factor for achieving the overall development goals. Afzal and Awais (2014) findings can be seen to imply the same as those of Klasen and Lawson (2007).…”
Section: Jhasssupporting
confidence: 80%
See 2 more Smart Citations
“…High population growth has become an important limiting factor for achieving the overall development goals. Afzal and Awais (2014) findings can be seen to imply the same as those of Klasen and Lawson (2007).…”
Section: Jhasssupporting
confidence: 80%
“…Examining the long-run benefits of population growth, the study by Simon (2019) found similar results with those of Afzal and Awais (2014) and Klasen and Lawson (2007) in the short run. Simon (2019) observed that an increase in population in the short run places a negative impact on the standard of living as a result of diminishing returns and the transient responsibility it places upon society.…”
Section: Jhasssupporting
confidence: 53%
See 1 more Smart Citation
“…Age structure (X4) is still another factor that is instrumental in increasing urban population. Afzal and Awais (2014) have reported that rural-urban composition has changed over the years. Fall in rural population and rise in urban population not only shows increase in population but also rising trend of migration to urban centers.…”
Section: Resultsmentioning
confidence: 99%
“…The results, conclusions and policy recommendation are difficult to be applied to Pakistan because socio-economic-political, geographical, demographic, law and order conditions differ significantly in Pakistan. Studies, have also been done in Pakistan (Shahbaz et al, 2010;Farah et al, 2012;Ahmad et al, 2013;Afzal and Awais, 2014). These studies have added valuable input to the urbanization issue in Pakistan.…”
Section: Significance Of Studymentioning
confidence: 99%